Descriptions of larvae of Vestalaria venusta (Hämäläinen, 2004) and Matrona basilaris Selys, 1853 (Odonata: Calopterygidae) - Wang, Runxi; Yu, Xin; Xue, Junli; Ning, Xin (Zootaxa, 2017)
Larva of Vestalaria venusta is identified using DNA barcoding match with the adult and described in the first time. Morphological characters are compared with those of Matrona basilaris and Vestalis amoena. The validity of genus the Vestalaria is reconfirmed. The important role of DNA barcoding in odonate larva identification is emphasized.